2021
DOI: 10.1111/jcmm.16713
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12/CXCR4 facilitates perineural invasion via induction of the Twist/S100A4 axis in salivary adenoid cystic carcinoma

Abstract: The activation of CXCL12/CXCR4 axis participated in the progression of multiple cancers, but potential effect in terms of perineural invasion (PNI) in SACC remained ambiguous. In this study, we identified that CXCL12 substantially expressed in nerve cells. CXCR4 strikingly expressed in tumour cells, and CXCR4 expression was closely associated with the level of EMT‐associated proteins and Schwann cell hallmarks at nerve invasion frontier in SACC. Activation of CXCL12/CXCR4 axis could promote PNI and up‐regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Among these factors, activation of CXCR4 by TWIST1 has been reported to play a role in cancer progression in various studies. [39][40][41] Based on the present data and on those available in the literature, we hypothesize that twist1 expression is strongly linked to factors in immunomodulation. We also explored the correlation between twist1 and immune checkpoints.…”
Section: Discussionsupporting
confidence: 73%
“…Among these factors, activation of CXCR4 by TWIST1 has been reported to play a role in cancer progression in various studies. [39][40][41] Based on the present data and on those available in the literature, we hypothesize that twist1 expression is strongly linked to factors in immunomodulation. We also explored the correlation between twist1 and immune checkpoints.…”
Section: Discussionsupporting
confidence: 73%
“…It has been reported that the CCL5/CCR5 axis could promote the migration, invasion and PNI of ACC (Gao et al, 2018). CXCL12/ CXCR4 participate in the course of EMT and Schwann-like differentiation in PNI and can promote ACC cell invasion and PNI through the Twist/S100A4 axis (Zhang et al, 2021). In addition, CCL20 enhances the anticancer response of the immune system by recruiting dendritic cells (Bonnotte et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting TWIST resulted in decreased cancer cell migration, invasion, and PNI ability, as well as a reduction in the expression of genes associated with EMT and Schwann cell markers. When S100A4 was overexpressed using a plasmid, researchers noted a significant growth in the migratory, invasive, and PNI ability of SACC cells, along with a more fibroblast-like appearance and an increase in pseudopodia formation [44].…”
Section: Twist Expression In Sacc and Its Significance In Pathogenesi...mentioning
confidence: 99%